Laceability in Hanoi Graphs (Journal of Informatics and Mathematical Sciences, 2019)
The topological structure of an interconnection network can be modelled by a connected, simple and undirected graph \(G=(V,E)\) where \(V\) represents the set of processors and \(E\) represents the set of communication links. Interconnection networks are used to interconnect the processors of data centres and cluster computers. The study of Hamiltonicity and the related areas such as Hamiltonian laceability and Hamiltonian connectedness has lot of significance in computer networks. A network(graph) is Hamiltonian connected if it contains a Hamiltonian path between two distinct nodes (vertices). In this paper we shall study the laceability properties associated with Hanoi graphs \(H_n\). To be more specific we shall explore Hamiltonian \(t^*\) connectedness of Hanoi graphs \(H_n\) for \(n\ge3\).
Keywords: Hamiltonian Laceability; Hamiltonian connected